Proposed Nutrient Standards for Plant-Based Beverages Intended as Milk Alternatives - Drewnowski, Adam; Henry, Christiani Jeyakumar; Dwyer, Johanna T. (Frontiers in Nutrition, 2021)
Background: Plant-based beverages (PBB) that are marketed as alternatives to cow milk are gaining in popularity worldwide. Nutrient quality of PBB can be highly variable. Objective: To develop a set of voluntary or mandatory nutrient standards for the PBB product category in order to assist innovation and guide product development and reformulation. Methods: The present goal was to develop standards for PBB energy content, minimum protein content and quality, maximum content for added fat, sugar, and salt, and to suggest fortification levels for selected vitamins and minerals. The standards were based on dietary recommendations and guidelines and current practices of federal agencies in the US. Results: The proposed energy and nutrient content for PBB milk alternatives are maximum 85–100 kcal energy per 100 g; a minimum for 2.2/100 g of high-quality protein, low content of saturated fat (<0.75/100 g) and added sugar (5.3–6.25/100 g) and consistent fortification with calcium, vitamins A, D, B-2, and B-12 at levels comparable to those found in cow milk (1%). Ideally, the protein content ought to be increased (2.8/100 g) and added sugar content reduced even further (2.7–3.1/100 g) for “best of class” products. These proposed standards were applied to the 641 existing PBB products listed in the 2018 version of the USDA Branded Food Products Database (BFPDB). The standards were met by <5% of the PBB on the US market. Conclusion: Often viewed as equivalent to milk in nutritional value, many PBB are often low in protein and are fortified with varying amounts of calcium, and vitamins A and D. Nutrient standards for this category should be adopted by the food industry, by public health regulatory authorities, and by standardization bodies such as the Codex Alimentarius.